Temperature-pattern informativeness in quality assurance - Vavilov V. P. Vladimir Platonovich (1987, 1987)
Temperature and thermal-radiation patterns are considered for thermal-monitoring problems. Spatial-frequency and spectral forms of filtration are discussed, as well as the comparison of amplitude and time criteria for defectiveness. Brief characteristics are given for thermal flaw detection and tomography.